Managerial aspects of obtaining pork in Romania - Bran, Mariana (Economics of Agriculture, 2010)
In the fight against poverty and world hunger, the most important issue for maintaining health, vitality and well-being of the human species is to provide animal protein. Thus, livestock - especially pigs - has gained a high share in ensuring the production of consumed meat, with variations from country to country. In Romania, pork is a product of basic food and in the consumer`s preferences, it occupies over 50% of the total consumption of meat. To ensure the necessary of pig meat, however, Romania has to import big quantities, situation detected in the European and national statistics. In order to achieve the production level requirements, it opted for: the promotion of improvement in the direction of the pig carcass, stimulation of pig farms to associate in order to represent their interests in the relationship with suppliers of inputs and finished products beneficiaries and to ensure their income by making goods for the export production.